Factors Influencing Smoking Behavior of Patients with Comorbid Hypertension : A Case Study of Community in The Area of Responsibility of Ramathibodi Hospital - Sriyoha, Nipawan; Saowanee, Rungtiwa (Journal of The Royal Thai Army Nurses, 2025)
This descriptive research aimed to study smoking behaviors and factors influencing smoking behaviors of patients with comorbid hypertension in the community under the responsibility of Ramathibodi Hospital, using the PRECEDE MODEL. The sample consisted of 100 patients with comorbid hypertension in the community under the responsibility of Ramathibodi Hospital, selected purposive sampling. Data were collected by questionnaire. Data were analyzed using descriptive statistics, Fisher exact probability test, Spearman rank correlation coefficient and non-parametric regression (NPR). The research results found that the majority of the sample group were male, age range 25-81 years, married, completed secondary education, general laborers, having income between 10,001-15,000 baht/month, income was not enough and required a loan, living in urban and crowded communities, smoking 10-20 cigarettes/day, moderate smoking behavior, predisposing factors (stress, knowledge, attitude and self-efficacy), reinforcing factor (social support) and enabling factor (community environment) did not influence smoking behaviors. However, it was found that the community environment was significantly related to smoking behaviors at the .05 significance level (Exact Sig.=.005). Recommendations: Smoking cessation programs and activities should be developed for hypertensive patients, involving the community in creating an environment conducive to improving smoking behaviors.